2010
DOI: 10.1103/physrevb.81.205439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ambient oxygen on the surface structure ofα-Cr2O3(0001)

Abstract: Surface x-ray diffraction has been employed to quantitatively assess the surface structure of ␣-Cr 2 O 3 ͑0001͒ as a function of oxygen partial pressure at room temperature. In ultrahigh vacuum, the surface is found to exhibit a partially occupied double layer of chromium atoms. At an oxygen partial pressure of 1 ϫ 10 −2 mbar, the surface is determined to be terminated by chromyl species ͑Crv O͒, clearly demonstrating that the presence of oxygen can significantly influence the structure of ␣-Cr 2 O 3 ͑0001͒.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
(42 reference statements)
3
17
1
Order By: Relevance
“…Numerical labeling of atoms is employed for identification purposes. Layer occupancies determined for Cr 2 O 3 –H 2 O UHV (current study) and Cr 2 O 3 –clean UHV 7 are indicated.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Numerical labeling of atoms is employed for identification purposes. Layer occupancies determined for Cr 2 O 3 –H 2 O UHV (current study) and Cr 2 O 3 –clean UHV 7 are indicated.…”
Section: Resultsmentioning
confidence: 93%
“…To begin the search for a structural solution, the clean surface structure (Cr 2 O 3 –clean UHV ) determined in recent quantitative LEED (LEED-IV) 15 and SXRD 7 studies was employed as a starting point. This surface exhibits a topmost partially occupied double layer of Cr atoms (Cr 0.31 –Cr 0.61 –O 2.4 – from LEED-IV, 15 and Cr 0.22 –Cr 0.31 –O 3 – from SXRD 7 ). Given that the current measurements were undertaken following exposure to ∼2000 L of H 2 O, terminations with surface Cr atoms bonded to one or more OH/H 2 O species were tested.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations